Pengembangan Aksesoris dari Bahan Air-Dry-Clay dan Resin di Surabaya - Jessica Ayumi Aris; Christian Anggrianto (Jurnal Vicidi, 2019)
The purpose of this research is to know the responses of potential customers in Surabaya to Accessories product made from Air-Dry-Clay dan Resin. The research method used is a Quantitative method by conducting questionnaires to 58 respondents and Qualitative methods to 5 Expert users, 3 Extreme users, online observing to 3 competitors, as well as literature and journal studies that can support this research. The result of the research can prove the fact that all women in Surabaya can use accessories they like. It is hoped that, this will require accessories that can be used by all age groups. Is an Air-Dry-Clay and Resin Accessories that can show the uniqueness with the pattern-play, shapes, and attractive color.